Probiotic in Cosmetics: A Patents Landscape Study: Life Sciences-Microbiology - Yadav, Narender; Ajmal, Gufran; Kumar Kumawat, Mukesh; Diwan, Anupama (International Journal of Life Science and Pharma Research, 2022)
Abstract: Probiotics, described as "live microorganisms that impart a health benefit on the host," are gaining popularity and are also valuable in the personal care industry. Probiotic are used in various cosmeceutical formulations such as anti-wrinkle, antiacne, and anti-ageing due to antimicrobial, antioxidant, anti-inflammatory, UV protection, and melanin synthesis inhibitor effects. In this work, a patent trend analysis of probiotic-based cosmetics patents is reported. In the last five years, patent filing has increased manifolds in this area. This study also discusses the inventions shown in the related patents with cosmeceutical compositions and their preparation methods. In conclusion, it has been found that probiotic in cosmetics still have numerous unexplored areas where innovation may flourish. The patent search was conducted using the commercially available CAS SciFinder database and the open-source patent database, The Lens. A total of 928 patents were found for search terms containing "probiotic" and "cosmetic" and retrieved from the database. After the initial screening, 38 patent documents were shortlisted for in-depth analysis. The analysis found that most of the top applicants come from the United States, the Republic of China, and the Republic of Korea, which shows market protection is more important in these countries. These countries lead the patent race in probiotic-based personal care products. The top applicants are related to private companies, universities, and people. The IPC code that has been recorded the most frequently (321 times) is A61K8/99, and it is related to cosmetics or similar toilet preparations from microorganisms other than algae or fungi. The research and development disclosed in most of the patents were focused on exploring or evaluating the mechanism of action of different probiotic strains and their application in skincare and beauty products. The most frequently used probiotic in topical formulations are Lactobacillus sp. and Bafidobacterium sp. Role of probiotics and mechanism of action for treating skin diseases such as skin whitening, skin moisturization, skin ageing, wrinkles, acne, psoriasis, rosacea, etc.